Measurement of D0, D+, D [star]+ and D+s production in pp collisions at √s=5.02 TeV with ALICE - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Ohlson, Alice; Pachmayer, Yvonne C.; Reygers, Klaus; et al. (The European physical journal. C, Particles and fields, 2019)
The measurements of the production of prompt $${D^0}$$ D 0 , $${D^+}$$ D + , $${D^{*+}}$$ D ∗ + , and $${D^+_{s}}$$ D s + mesons in proton-proton (pp) collisions at $$\sqrt{s}=5.02~TeV$$ s = 5.02 TeV with the ALICE detector at the Large Hadron Collider (LHC) are reported. D mesons were reconstructed at mid-rapidity ( $$|y|<0.5$$ | y | < 0.5 ) via their hadronic decay channels $$D^0 → K^-π ^+$$ D 0 → K - π + , $$D^+→ K^-π ^+π ^+$$ D + → K - π + π + , $${D}^{*+} → D^0 π ^+ → K^- π ^+ π ^+$$ D ∗ + → D 0 π + → K - π + π + , $${D^{+}_{s}→ φ π ^+→ K^{+} K^{-} π ^{+}}$$ D s + → ϕ π + → K + K - π + , and their charge conjugates. The production cross sections were measured in the transverse momentum interval $$0<36~GeV/c$$ 0 < p T < 36 GeV / c for $${D^0}$$ D 0 , $$1<36~GeV/c$$ 1 < p T < 36 GeV / c for $${D^+}$$ D + and $${D^{*+}}$$ D ∗ + , and in $$2<24~GeV/c$$ 2 < p T < 24 GeV / c for $${D^+_{s}}$$ D s + mesons. Thanks to the higher integrated luminosity, an analysis in finer $$p_{T}$$ p T bins with respect to the previous measurements at $$\sqrt{s}=7~TeV$$ s = 7 TeV was performed, allowing for a more detailed description of the cross-section $$p_{T}$$ p T shape. The measured $$p_{T}$$ p T -differential production cross sections are compared to the results at $$\sqrt{s}=7$$ s = 7 TeV and to four different perturbative QCD calculations. Its rapidity dependence is also tested combining the ALICE and LHCb measurements in pp collisions at $$\sqrt{s}=5.02~TeV$$ s = 5.02 TeV . This measurement will allow for a more accurate determination of the nuclear modification factor in p-Pb and Pb-Pb collisions performed at the same nucleon-nucleon centre-of-mass energy.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel sind "0", "star" und "+" hochgestellt
Bei "D+s" ist das Zeichen "+" hoch-, der Buchstabe "s" tiefgestellt
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, A. Ohlson, Y. Pachmayer, K. Reygers, A. Schmah, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 17.02.2020